2010
DOI: 10.1159/000320690
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Frequency of p53 Gene Alterations in Gastritis Lesions from Iran

Abstract: Background: It has been frequently shown that p53 alterations have an important role in the development of gastric cancers but there is no data on p53 alteration in gastric cancer and its precancerous lesions from Iran although this country experiences one of the highest gastric cancer incidence and mortality rates in the world. The purpose of this study was to do a comprehensive assessment of p53 alterations in the Iranian population of gastritis patients and to evaluate the association between p53 alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(42 reference statements)
0
3
1
Order By: Relevance
“…Ultimately, our previous work on gastritis showed that the CG to TA transition was relatively rare in CpG codons of the p53 gene, which was contrary to the findings of other work . We attributed this phenomenon to DNA hypomethylation in the body of p53 gene because the rate of deamination of cytosine is considerably less than methylated cytosine.…”
Section: Introductioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Ultimately, our previous work on gastritis showed that the CG to TA transition was relatively rare in CpG codons of the p53 gene, which was contrary to the findings of other work . We attributed this phenomenon to DNA hypomethylation in the body of p53 gene because the rate of deamination of cytosine is considerably less than methylated cytosine.…”
Section: Introductioncontrasting
confidence: 64%
“…GC → AT transition in the p53 gene is commonly seen in gastric carcinoma, and transition in the CpG dinucleotides accounts for more than half of GC → AT mutations . However, in our previous work on gastritis, we found that CpG codons 9, 245 and 248 underwent GC → TA transversion, so our hypothesis suggesting the global hypomethylation of the genome during gastritis development encouraged us to assess the probable correlation between global genome hypomethylation and alterations at CpG codons of the p53 gene.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations